Impact of Remittance on Educational Outcomes: Empirical Evidence from Nepal (Dristikon: A Multidisciplinary Journal, 2024)
The remittances are the treasure for irrigating Nepal's economy. Because emigration is increasing, per capita remittance is also increasing in Nepal. However, the question is signaling in its utilization for educational attainment. In this context, the study examines the impact of remittance on educational outcomes in Nepal. The study applied autoregressive distributed lag (ARDL) estimations, Granger causality, forecast error variance decomposition (FEVD) technique, and impulse response functions (IRFs), with time-series data spanning from 1981 to 2021. The overall findings revealed that remittance had a positive impact on educational outcomes in Nepal. In the short run, remittance was found to be crucial for secondary schooling; in the long run, remittance had a significant effect on tertiary schooling in Nepal. The FEVD confirmed that remittance might be the inevitable predictor of educational outcomes in Nepal. The Granger causality also found a unidirectional causality from remittance to educational outcomes. The policymakers and stakeholders, therefore, should focus on funneling remittance toward financing education as well as a productive sector to accelerate per capita GDP and on cropping the demographic dividend in the Nepali economy.